6a(-2a+3)=

Simple and best practice solution for 6a(-2a+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a(-2a+3)= equation:


Simplifying
6a(-2a + 3) = 0

Reorder the terms:
6a(3 + -2a) = 0
(3 * 6a + -2a * 6a) = 0
(18a + -12a2) = 0

Solving
18a + -12a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '6a'.
6a(3 + -2a) = 0

Ignore the factor 6.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(3 + -2a)' equal to zero and attempt to solve: Simplifying 3 + -2a = 0 Solving 3 + -2a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2a = 0 + -3 -2a = 0 + -3 Combine like terms: 0 + -3 = -3 -2a = -3 Divide each side by '-2'. a = 1.5 Simplifying a = 1.5

Solution

a = {0, 1.5}

See similar equations:

| 6m-1=-4+5m | | (-x+9)(-8-11x)=0 | | z+16=33 | | 2h+6=56 | | -(3x-5)-(2x-6)+1=-(12x+5)-(3x+2)+3 | | 7.68x+4=58.9824+2x | | -7u=-28 | | (4-9x)(2-5x)=0 | | b-a=-5 | | m^2+9=73 | | 8.8a+14=119.6 | | s-5=25.58 | | 90+b=a | | 1-5v+7v=-27 | | 2.32x+11.6=23.2 | | -27=1+x+6x | | -7x=-5+15x-(-x-5) | | -3=14-11n-6n | | 13n-239=4n-14 | | -7x=-5+15x-(x-5) | | 2(v-6)=4v-16 | | -12q+4=89-6 | | 4+3=223 | | (x-y)-90=0 | | 9(7x+8)+3(x+10)= | | m-12+4m=13 | | 7x-4x=-36 | | 5-7x-8+14x-17=10x-4x-3 | | 6x+8=-37-3x | | 1-3k-13=30 | | 5-7x-8+14x-17=11-2+5+28-10+18 | | 2X^4+3X^3+X^2=0 |

Equations solver categories